Strategi Digital Marketing: Pengaruh E-WOM dan Iklan Media Sosial terhadap Niat Beli Konsumen Produk Kosmetik - Sovi Iriyanti; Harmanda Berima Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of Electronic Word of Mouth (E-WOM) and social media advertising on consumers' purchase intention. The research employs a quantitative method. It involves 146 respondents who intend to purchase cosmetic products from a specific brand in Semarang City. The data were analyzed using multiple linear regression analysis with SPSS. The regression analysis results indicate that Electronic Word of Mouth (E-WOM) has a positive effect on consumers' purchase intention, and social media advertising also positively influences consumers' purchase intention.